Calculation of efficiency in a centrifugal pump using the thermodynamic method through an adapted voltage acquisition module - Erick O. Castañeda Magadán; Laura L. Castro Gomez; José A. Marbán Salgado; Miguel A. Basurto Pensado; Víctor M. Zezatti Flores; Oscar Sotelo Mazón (Measurement: Sensors)
This study presents the calculation of hydraulic efficiency in a variable-speed centrifugal pump using the Thermodynamic Method, employing a cost-effective, adapted data acquisition system to obtain key variables. The proposed equipment complies with the criteria established by the “International Electrotechnical Commission (IEC) 60041” Standard for applying the Thermodynamic Method to the pump. Temperature and pressure measurements at the suction and discharge section of the turbomachine provide real-time data for hydraulic efficiency calculation. The temperature and pressure (key variables) are recorded through an open access system integrated with commercial software that offers a user-friendly interface. Experimental tests conducted at different rotational speeds in the pump allow for the efficiency curves based on the temperature difference between the pump's inlet and outlet. The results indicate a maximum hydraulic efficiency of 50.52 % at a rotational speed of 276 rad/s with an error of 1.65 % compared to the theoretical efficiency and an average error of 7.49 % across the entire rotational speed range (220 rad/s – 371 rad/s). With an error margin below 10 % across the tested rotational speed range, the adapted module ensures reliable efficiency results for water temperatures ranging from 20 °C to 46 °C.